UM MODELO DE SISTEMA DE FILTRAGEM HÍBRIDA PARA UM AMBIENTE COLABORATIVO DE ENSINO APRENDIZAGEM - SANTOS, André Luis Silva dos (2008)
Nowadays, the World Wide Web (WWW) is an excellent source of information. However, open issues carry on. It´s difficult obtain relevant information in short time. Moreover, there is no accuracy for retrieving this information. Servers such as Google, Altavista and Cadê, can retrieve a huge amount of information. Nonetheless, the retrieved information could be not relevant. The information filtering systems arise to aim users in the searching for relevant information. This work proposes a hybrid model of filtering information based on content-based filtering and collaborative filtering. This model has been used into a collaborative learning system named NetClass and it was developed using the PASSI methodology. A case study done with CEFET´s students is presented as well.